Analysis of the direct benefits of timber and fisheries in the mangrove forest of Babulu Laut Village, North Penajam Paser Regency - Kristiningrum, Rochadi; Rujehan; Purwanti, Emi; Setiawati; Kusuma, Rudi (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Mangrove forests are one of the natural resources of coastal areas that have an important role in terms of social, economic, and ecological aspects. The values contained in mangrove forests can be evaluated economically using the economic valuation method. This study aims to determine the direct benefits and economic value of direct benefits from mangrove forests in Babulu Laut Village. Method: The time needed for this study is more or less effective starting from April 2023 – November 2023. The sampling technique or key respondents as many as 1 respondent and case respondents were carried out by accidental sampling as many as 41 respondents. Data processing and analysis using qualitative descriptive analysis methods and quantitative descriptive analysis with economic valuation methods. Data types are primary and secondary data. Result: From the results of this study shows that the direct benefits in the mangrove forest of Babulu Laut Village which has an area of approximately 1,000 ha, namely the benefits of wood and the benefits of fisheries consisting of the benefits of fish, shrimp, crabs and seaweed. The total value of direct benefits of mangrove forests in Babulu Laut Village is Rp.404,069,141,162.00/year, this value consists of wood benefits with income of Rp.69,166,666,667/year, fish with income of Rp.40,085,011,187.00/year, shrimp with income of Rp.63,932,374,635.00/year, crabs with income of Rp.34,075,518,808.00/year, seaweed with income of Rp.196,809,569,866.00 per year. Conclusion: The greatest value of direct benefits is obtained from seaweed products, while the smallest income comes from crab benefits. Novelty/Originality of this study: This study presents the comprehensive economic valuation of the direct benefits of mangrove forests. It provides an in-depth understanding of the economic contribution of various mangrove forest products to local communities. The findings provide an empirical basis for decision-making in sustainable mangrove forest management by highlighting the economic potential that needs to be optimally exploited, particularly in the seagrass sector.